An Integrated Technique to Ensure Confidentiality and Integrity in Data Transmission Through the Strongest and Authentic Hotspot Selection Mechanism - Bhattacharjee, S. (Springer, 2020)
Wireless technology has consistently been a popular resolution for handling the growing demand of data receiving in mobile linkages as the availability of high-speed internet is increasing rapidly. Although, the legacy of such technology shortages of seamless inter-communication amid the wireless link as well as mobile cellular linkages on one individual pointer as well as among the wireless hotspots conversely. Subsequently, data confidentiality and integrity are also primary concerns in data transmission through any network. There can be various weak and strong hotspots, since it is also possible to have fake hotspot in any network. A number of researches have been conducted to ensure data security by selecting the strong and authentic hotspot in wireless network infrastructure. However, the present literature fails to offer any security mechanism that can select the strongest, authentic hotspot and secure data confidentiality as well as integrity at the same time. Hence, this research aims to build an integrated technique that can offer adequate level of data confidentiality and integrity along with the selection of a strongest and most authentic hotspot. The proposed integrated technique comprises a unique hotspot selection and a SDES-based authentication mechanism to establish a secure communication link by picking the strongest hotspot. It encrypts the input data with SDES to assure confidentiality and uses an idle error checking technique with a backup scheme for fortuitous information loss to protect data integrity during transmission. The experimental results show its superiority over other existing techniques by improving QoE demands and fairness matrices. It offers higher avalanche effect and entropy values which justify its capacity to offer adequate data confidentiality. The capacity to offer lower percentage of information loss proves its efficiency in offering data integrity. Â© 2020, Springer Nature Singapore Pte Ltd.